(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: Smoking is recognized as a major public health problem in the world. Materials & Methods: The objective of the study was to assess the prevalence and determinant of adolescent smoking in West Kafrul Dhaka. This was a cross sectional study conducted in 2013 among 150 adolescent boys of school and slum. Results: The results showed 35.33% adolescent boys had smoking habit. Most of the adolescent (86.79%) had started smoking when they were 14-17 years old. This study found that peers influence (50.94 %) was the most common causes of smoking. Among the boys who live in slum, 80% were smoker and among the school going boys 15% were smoker. Conclusion: Smoking was very common among middle-class male teenagers and even more prevalent among youths from nearby slums. Awareness program on tobacco will be an effective way to control. Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 34-38